Characteristics of coal oxidation and spontaneous combustion in Baishihu Mine, Xinjiang, China - Zhang, Wanling; Zeng, Qiang (Frontiers in Earth Science, 2023)
The characteristics of oxidized spontaneous combustion of coal can reflect the performance of coal, and the appropriate structural model can reflect it more intuitively. In this study, coal samples from Baishihu Coal Mine were used. The macromolecular structure, microcrystal structure and oxidation process of coal samples were studied by XPS, 13C-NMR and FTIR. The results convey that the molecular formula C198H164O40N2 and the molecular structure model were obtained. Chemdraw and Materials Studio were used for the experimental data, and high-resolution transmission electron microscopy (HRTEM) was used to verify the aromatic ring structure built the constructed structural model more accurate. In the water evaporation stage, the high ring aromatic layer is converted into the low ring number. And in the high-temperature stage, the low ring aromatic layer is transformed due to the coking and condensation reaction of the coal sample. The C element in the coal sample mainly participates in the reaction in the C-C and C-H forms. The spacing and effective number of aromatic layers are relatively stable. The aggregation state of coal is a macromolecular group formed between molecules with different aromatic structures and fat structures, which is formed by the interaction of internal defects and pores of molecular groups. With the expand in treatment temperature, water loss is heavier, oxygen absorption and weight gain are perplexing, and the value of burnout temperature is higher. The apparent activation energy of the coal oxygen reaction increases, and the reaction is more intricate, to achieve. This study provides a reference for further studying the properties and oxidation combustion characteristics of Hami coal in Xinjiang.